Synthesis, characterization, crystal structures and fungicidal activity of some copper(II) carboxylates with 3-hydroxypyridine - Golobič, Amalija (Acta chimica slovenica, 2006)
Different synthetic routes were applied for preparation of some copper(II) carboxylates with 3-hydroxypyridine (3-pyOH). Monomeric and dimeric complex of copper(II) acetate were isolated, Cu(O2CCH3)2(3-pyOH)2, 1, and Cu2(O2CCH3)4(3-pyOH)2, 2, respectively. A covalently linked 2D CuII compounds of general formula Cu(O2CR)2(3-pyOH)2n, were prepared with benzoate (R=C6H5, 3), hexanoate (R=CH3(CH2)4, 4), and heptanoate (R=CH3(CH2)5,5) ligands. The crystal structures of all five compounds were determined by X-ray structure analysis. The compounds were tested for fungicidal activity against two fungal species Trametes versicolor and Antrodia vaillantii. Complete growth retardation for Antrodia vaillantii was noticed for compounds 3, 4, and 5 at concentrations of 5 10-3 mol L-1, 1 10-3 mol L-1, and 5 10-4 mol L-1, while in the case of Trametes versicolor completegrowth retardation was observed for the same three compounds only at the highest tested concentration.
Keywords: anorganska kemija; baker; karakterizacija; karboksilati; koordinacijske spojine; kristalna struktura; piridini; rentgenska strukturna analiza; sinteza; strukturna kemija